2SPD-033 Making the case for pre-filled syringes: development and utilisation of an economic model. (23rd March 2022) - Postma, MJ; Weiss, M; Edwards, T; Girgis, H; Cribbs, K; Acker, E; Lahue, B
Abstract : Background and importance: Parenteral medication is primarily delivered via conventional vial or ampoule and syringe in hospital settings; however, prefilled syringes (PFS) offer economic and clinical advantages, including reductions in preventable adverse drug events (pADEs), drug waste and supply costs, and increases in workflow efficiencies. The benefits of converting from vials and ampoules to PFS (denoted as 'V2P' hereafter) have been elucidated in previously developed economic models; however, these models are country-specific, therefore limiting generalisability of findings. Aim and objectives: To examine the potential impact of V2P, an economic model was developed to provide hospitals with a standardised tool for use across acute and emergency clinical settings. Material and methods: The Excel-based economic model estimates the potential benefit of V2P related to four key outcomes: pADEs, labour–time efficiency, unused drug, and cost of supplies. Built-in model defaults were derived from existing peer-reviewed literature sources, expert interviews, and national datasets. The model user can input specific information related to the hospital department and drug of interest. Users may also change built-in model defaults. To investigate model utility, a hypothetical case study was conducted focusing on atropine administration in a UK cardiac intensive care unit (ICU) administering 35 doses/day of atropine. Literature-based inputs included drug costs of £0.82/ampoule dose and £5.03/PFS dose and vial drug waste levels at 85%. The built-in assumptions were 1.39 and 0.73 pADEs per 100 administrations for vials and PFS, respectively. Results: In the hypothetical case study, annual V2P cost savings associated with reductions in pADEs, unused drug, and costs of supplies were £64 126, £59 361 and £2667, respectively. While the annual cost of PFS was £53 783 greater than vials, the net budget savings of V2P was £72 372 per year. Additionally, preparation time decreased 893 hours per year. Full results will be presented. Conclusion and relevance: The model provides a generalisable framework with customisable inputs, allowing hospitals in any country to quantify the clinical and economic value of adopting PFS. In a hypothetical cardiac ICU switching from atropine ampoules to PFS, despite increased cost per dose with PFS, the analysis documented reductions in medication preparation time and a net budget savings owing to fewer pADEs and reduced drug wastage. References and/or acknowledgements: Conflict of interest: Corporate sponsored research or other substantive relationships: MJP received grants and honoraria from various pharmaceutical companies, inclusive of those interested in the topic of this abstract. MW, HG and TE are employees of Becton Dickinson. Alkemi LLC received consultancy fees to advise on study design, data analysis and interpretation.